The Online Gambling as a Criminal Offense Which Disturbs Society on Legal Perspective - Rr dijan widijowati; Rowela Cartin Pecson; Kristiawanto Kristiawanto (Unissula, 2025)
Online gambling has become a global phenomenon that has gained increasing attention in recent years. Advances in technology and easy access to the internet have allowed individuals to engage in gambling activities without being bound by geographical boundaries. However, these developments have also brought significant negative impacts, including complex legal issues associated with online gambling. This study seeks to provide an in-depth assessment of Indonesia's affirmative law regarding online gambling as a criminal offense. The research methodology used is the normative legal research method, with data collection carried out through a literature review. The main focus of this study is to analyze the legal aspects related to online gambling in Indonesia. The research findings indicate that Indonesian positive law has strictly regulated gambling and tends to prohibit it. However, online gambling presents unique challenges for law enforcement, especially due to its cross-border and difficult-to-track nature. This study provides a deeper understanding of the legal challenges facing Indonesia in addressing online gambling as a criminal offense, the need for stronger international cooperation in addressing illegal online gambling, as well as better tools and more effective law enforcement policies. Finally, the criminalizing online gambling is to provide legal sanctions to perpetrators, prevent the spread of gambling, protect society from its negative impacts, and uphold moral values and prevailing social norms. This criminalization also aims to provide a deterrent effect for perpetrators and prevent others from getting involved in online gambling.